Modele badań nad kulturą szkoły = Models of research on school culture - Śliwerski, Bogusław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The category of "school culture" has permeated school pedagogy from other social sciences. It is a key commitment for educational reforms to unschool this institution, i.e. to make it more humane. The article presents scientific analyses on the subject, unknown in Poland, which may be useful in the design of research projects. It is important that researchers do not introduce in their diagnoses approaches taken directly from the management sciences, which concern a completely different sphere of organisational activity in open societies which subject the economy to free market competition. The school cannot be subjected to solutions aimed at more efficient production, because the role of education is to involve children and young people in culture. Therefore, the school must be a carrier of its features.
Keywords: kultura; kultura szkoły; innowacje; reformy szkolne; edukacja; rozwój; doskonalenie; wartość; culture; school culture; innovation; school reforms; education; development; improvement; values